ESP DEBATE: Is Belief in ESP Irmtional? - PINKER, STEVEN; JOSEPHSON, BRIAN D. (Skeptic, 2022)
The article highlights on three-part debate between Steven Pinker and Brian D. Josephson, in itiated from a private email exchange in which Josephson challenged Pinker's claims in a BBC radio program that there is no rational reason to believe in ESP. This admittedly purple prose drew objections from the biologist Rupert Sheldrake and the Nobel prize-winning physicist Brian Josephson.